Extensive sampling sheds light on species-level diversity in Palearctic Placobdella (Annelida: Clitellata: Glossiphoniiformes) - Kvist, Sebastian; Utevsky, Serge; Marrone, Federico; Ben Ahmed, Raja; Gajda, Lukasz; Grosser, Clemens; Mueller, Christian (Springer, 2022)
The bloodfeeding leech genus Placobdella is dominated by North American diversity, with only a single nominal species known from Central America and one from the Palearctic region. This is likely due to considerable underestimation of Palearctic biodiversity, but investigations into potential hidden diversity are lacking. To shed light on this, the present study introduces new data for specimens initially identified as Placobdella costata from Ukraine (close to the type locality), Italy, Germany, Latvia, Montenegro, Bulgaria, Slovenia, Turkey, Azerbaijan, Tunisia, and Algeria, and uses both nuclear (Internal Transcribed Spacer [ITS] region) and mitochondrial (cytochrome c oxidase subunit I [COI]) sequence data in phylogenetic and DNA barcoding frameworks, in order to better understand species-level diversity. Seven independent lineages are present in the trees, five of which show adequate separation at the COI locus to suggest their unique species-level status (COI distances between these clades range from 4.86 to 8.10%). However, the ITS data suggest that speciation is recent or incipient in these clades, and that not enough time has passed for clear separation at this locus. We discuss the evolutionary and taxonomic implications of our findings and speculate on dispersal events that may have contributed to shaping this pattern of geographic distribution.
Keywords: Hirudinea; Placobdella costata; Cytochrome c oxidase subunit I; Internal Transcribed Spacer; Genetic variation; Biodiversity